NOVEL PRINCIPLES OF MICROWAVE BAND RADIOELECTRONIC DEVICES DESIGN WITH THE USE OF MICROWAVE PHOTONICS TECHNOLOGY - M. E. Belkin; S. A. Kudzh; A. S. Sigov (Российский технологический журнал)
There are highlighted fundamental and practical advantages referred to introduction of the new interdisciplinary scientific and technological direction, that is, microwave photonics, in modern and perspective radio means of a dual purpose. The main advantages consist in increase of operating frequency to terahertz range, expansion of a processing band to several gigahertz, improvement of electromagnetic compatibility and mass-volume characteristics. A classification of the component base of microwave photonics is proposed, the modern level of world development of microwave photonics with emphasis on its second stage, which is integrated microwave photonics, is analyzed. The works in the field of microwave photonics that have been performed or being conducted by research groups at Moscow Technological University, including results of modeling and research projects, training, and the nearest tasks of the established Scientific and Technological Center «Integrated Microwave Photonics» are briefly described.